Evil under the sun [videorecording (DVD)] - Horowitz, Anthony, 1955-; Suchet, David; Fraser, Hugh; Jackson, Philip, 1948-; Moran, Pauline; Tammes, Fred, 1937-; Gunning, Chris; Christie, Agatha, 1890-1976 (Agatha Christie's Poirot, 2001)
During a doctor ordered rest at a resort, Poirot fears a fellow visitor may die, and a woman is found dead. Poirot becomes involved with solving the mystery of her murder.